Isolation and Identification of Pyrene-degrading Bacteria from Soils around Landfills in Shiraz and Their Growth Kinetic Assay - Farshid Kafilzadeh; Fatemeh Hoshyaripour; Razieh Afrough; Hoshanq Jamali; Ghader Allahverdi (Fasa University of Medical Sciences, 2011)
Background & Objectives: Pyrene is a kind of carcinogen hydrocarbon in environment and one of the top 129 pollutants as ranked by the U.S.Environmental Pretection Agency (USEPA). Today's commodious method that is considered by many researchers is the use of microorganisms to degrade these compounds from the environment. The goal of this research is separation and identification of the indigenous bacterias which are effective in decomposition of Pyrene hydrocarbon from soils around Shiraz Landfills. Isolated bacteria growth in the presence of different concentrations of the aforesaid organic pollutant was evaluated. Materials & Methods: Taking samples from Landfills were done after transportation them to the laboratory. The numbers of the bacterias were counted in a medium including Pyrene 0.6 g/l and in another medium without Pyrene. The isolated bacterias were separated by the enriched medium of hydrocarbon Pyrene and were recognized accordance with standards methods (specialty of colony, microscopic properties, fermentation of sugars and biochemical test).The kinetic growth of the separated bacterias was evaluated every 12 hours during 7 successive days. Results: It was reported that the numbers of the bacterias in the medium without Pyrene is more than those with Pyrene (cfu/g). The separated bacterias were included Bacillus spp., Pseudomonas spp., Micrococcus spp., Mycobacterium spp. These four isolated bacterias showed the best growth with Pyrene 0.6 g/l during third and fourth days. Conclusion: The separating bacterias, effecting in decomposition of PAH, make this possibility that the modern methods with more efficiency to be created for removing the carcinogen organic polluters from the environment. Moreover, the separated bacterias (relating to this research) can be applied to develop the microbial population in the areas that polluted with Pyrene.